Case report: Medical student types journals during ketamine infusions for suicidal ideation, treatment-resistant depression, post-traumatic stress disorder, and generalized anxiety disorder - Willms, Joshua; McCauley, Ben; Kerr, Lindsay; Presto, Peyton; Arun, Ankith; Shah, Nazeen; Irby, Kierra; Strawn, Megan; Kopel, Jonathan (Frontiers in Psychiatry, 2022)
Suicide is the most common cause of death in male resident physicians and the second most common cause of death in resident physicians overall. Physicians also experience high rates of major depressive disorder (MDD), post-traumatic stress disorder (PTSD), and burnout. These conditions frequently develop during medical school, and threaten not only physicians but the patients they care for. A 30-year-old medical student presented to our clinic with a history of treatment-resistant depression (TRD), generalized anxiety disorder (GAD), PTSD, and five years of daily suicidal ideation. Previous treatments included therapy, lifestyle modifications, and various combinations of six antidepressants. These interventions had little effect on the patient's mental health. The patient was treated at our clinic with an 8-month regimen of IV ketamine infusions and ketamine-assisted psychotherapy (KAP). The patient achieved remission from suicidality and PTSD within one month; and TRD and GAD within seven months. The patient’s Patient Health Questionnaire (PHQ-9) score decreased from 25 (severe depression) to 1 (not depressed). These findings suggest that ketamine and KAP may represent effective interventions for mental health applications in healthcare professionals. The patient made the unique decision to attempt to type narrative journals during four of his ketamine infusions (doses ranged from 1.8 to 2.1 mg/kg/hr IV). The patient successfully typed detailed journals throughout each 1-hour ketamine infusion. To our knowledge, these journals represent the first independently typed, first-person, real-time narratives of ketamine-induced non ordinary states of consciousness. The transcripts of these journals may provide useful insights for clinicians, particularly in the context of KAP.